PTH-100 Nice Guidance on The Treatment of Hepatitis C (HCV) Genotype 3 (G3) – Have We Forgotten The Past? Single Centre Experience of Biopsy Proven Fibrosis in HCV G3 Suggests Slower Progression than Previously Suggested. (17th August 2016) - Fairbrass, K; Forrester, K; Fenton, L; Simpson, R; Moreea, S
Abstract : Introduction: NICE guidance in 2000 (TA14) only recommended treatment of patients with moderate/severe HCV. NICE now advises that patients with G3 early disease should not be given DAAs but be treated with pegylated interferon/ribavirin, which is a longer treatment with lower SVR and more side effects. Methods: Our databases were used to obtain: demographics, age at point of liver biopsy, stage of fibrosis and SVR in relation to all genotypes. We aim to plot the rate of progression of fibrosis in HCV G3 patients to ensure NICE guidance isn't disadvantageous to this group. Results: Between 1998–2015 we biopsied 477 patients: G1 112(81 males average 40 years, 31 females average 42 years) SVR 48%; G2 16(10 males; average 39 years, 6 females average 43 years) SVR75%; G3 337 (194 males average 39 years, 143 females average 40 years) SVR 68%; G4 12(10 males average 38 years, 2 females average 45 years) SVR 42%. The point prevalence of fibrosis in HCV G3 at the time of liver biopsy is shown on the graph along with the SVR in relation to the stage of fibrosis. This confirms that fibrosis progresses with age but not in an exponential way and also recognises the well described fall in SVR with increasing fibrosis. Conclusion: We confirm HCV G3 progresses in both males and females from the mid-40s. Our SVR data strongly suggests that we should provide all of our HCV G3 patients with the new potent DAAs to prevent progression of disease and subsequent consequences. We urge for a change in the current guidance. Disclosure of Interest: None Declared